My story : a photographic essay of life with multiple sclerosis - Davis, Amelia, 1968- (New York : Demos, 2004)
My Story is an evocative description of what it is like to live with multiple sclerosis (MS), a disease that affects about 350,000 Americans and whose cause is still not entirely known. The essays and accompanying photographs in this highly engaging, beautifully illustrated book poignantly portray the lives of thirty-two men and women from the ages of seventeen to seventy and of various ethnicities and backgrounds who share the challenge of living with MS.
Keywords: Multiple sclerosis -- Patients -- Biography; Multiple sclerosis -- Patients -- Biography -- Pictorial works